Does direct cash flow presentation help in predicting future operating cash flow? - Simões, Flavio Manuel Vilas-Boas (2012)
Research literature and regulators are unconditional in pointing the disclosure of operating cash flow through direct method a section of unique information. Besides the intuitive facet, it is also consistent in forecasting future operating cash flows and a cohesive piece to financial statement puzzle. Bearing this in mind, I produce an analysis on the usefulness and predictive ability on the disclosure of gross cash receipts and payments over the disclosure of reconciliation between net income and accruals for two markets with special features, Portugal and Spain. Results validate the usefulness of direct method format in predicting future operating cash flow. Key